FACTORS AFFECTING CAPITAL STRUCTURE ON REGIONAL COMPANY OF BKK RURAL BANKS IN SUKOHARJO REGENCY - Hadi Samanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
The analysis result shows that sales positively affect the capital structure, it means that more sales increase is financed by debt. The asset structure does not positively affect the capital structure, it means that additional current assets are more financed from debt.Profitability has no negative effect on capital structure, it means that profits earned by the company can be partially replanted into the company to increase their own capital. Growth does not negatively affect the capital structure, it means a declining growth rate from year to year due to limited own capital, so asset growth is still financed by debt.Based on the F tests, it shows the sales, asset structure, profitability, growth affects the capital structure simultaneously. Coefficient of determination R², Adjusted R Square value is obtained which shows sales, asset structure, profitability, and growth can explain the structure of capital, the remainder is explained by the residual variable or outside of this study. Keywords: sales, asset structure, profitability, growth, and regression linear multiple.